Google scholar citation analysis - Xu, Ai (2014)
Google Scholar (GS) is one of the web search engine for scholarly literation across many disciplines and source which allows users to access the database freely. GS also keep track the citations of the author’s publications and calculate h-index for authors. Citation impact measures influence of a particular article, while h-index measures the influence of a particular author. However, GS calculate both citation and h-index statistics including self-citation articles. From research data shows that with the count of self-citations, this helps to improve the number of citations and h-index significantly but it contradicts the intension of using citation count and h-index to reflect one’s research impact. With high self-citation count in the publication, this does not reflect the true research impact.